Screen‐Printed Electrodes for Amperometric Determination of Iodide. Issue 2 (19th November 2014) - Khodari, M.; Bilitewski, U.; Basry, A. A. H.
Abstract An amperometric method for the determination of iodide ions has been developed using disposable, screen‐printed electrodes. The used sensors have a gold, graphite and platinum working electrodes with an area of about 7 mm2. Calibration curves exhibit a linear relationship between the electrode response and the iodide concentration up to 3.00 mM. The correlation coefficients for all calibration curves varied from 0.988 to 0.998. The relative standard deviations were equal to or less than 5.26 % (n=5). The lowest iodide concentration measured was 100 µM.